Development of E-Learning Web for ITB AAS Indonesia Using CodeIgniter Framework - Muqorobin, Muqorobin; Sumadi, Sumadi; Fitria, Tira Nur (International Journal of Computer and Information System (IJCIS), 2024)
With the rapid advancement of information technology, the need for effective educational platforms has become pressing. ITB AAS Indonesia has taken steps to meet this need by developing an e-learning system using the CodeIgniter framework. This paper discusses the development process of the e-learning platform designed to provide an enhanced learning experience for students and faculty. By adopting a user-centered approach and applying structured development methods, this system offers advanced features that support remote learning, user interaction, and educational content management. Evaluation results indicate that this platform enhances accessibility and efficiency in the teaching and learning process, significantly contributing to modern education in Indonesia.